COMPARISON OF THE CONCEPTS OF “LIFELONG LEARNING” AND “LIFELONG EDUCATION - Batisteti, Éverton Madaleno (2021)
In this theoretical essay, a comparison was made between the concepts of Lifelong Education and Lifelong Learning. We sought to use the concepts in reports that impacted education worldwide and its genesis in Confintea. As already reported by other researchers internationally, there is a misuse of one concept as a synonym for the other. It is suggested that these concepts differ in defense of humanistic training or in the development of holistic conditions for the consolidation of learning and the development of human capital. It is understood as necessary to be clear about the concept of Lifelong Learning, already present in the Law of Directives and Bases No. 9394/1996 through the amendment of Law No. 13632/2018, and widely disseminated at an international level. This conceptual precision can help all researchers and scholars on the subject to develop research, teaching and extension in line with their own theoretical interests. At the end, there is a comparative table and suggestions.